Accuracy and cost effectiveness of a waferless osteotomy approach, using patient specific guides and plates in orthognathic surgery: a systematic review. Issue 5 (June 2022) - Williams, A.; Walker, K.; Hughes, D.; Goodson, A.M.C.; Mustafa, S.F.
Abstract: The aim of this systematic review is to evaluate the accuracy of waferless osteotomy procedures in orthognathic surgery with a secondary aim to determine the cost-effectiveness of the procedure. A literature search was conducted on the databases PubMed and Scopus, with PRISMA guidelines followed. An initial yield of 4149 articles were identified, ten of which met the desired inclusion criteria. The total sample of patients undergoing waferless osteotomies included in this review was 142 patients. Nine of the studies used surgical cutting guides along with customised surgical plates to eliminate the surgical wafer and one study used pre-bent locking plates instead of customised plates. The eligible articles determined their surgical accuracy by comparing the positions of bony or dental landmarks on the pre-operative and post-operative images. The articles all reported acceptable accuracy within previously established clinical parameters. The majority of authors concluded that it is an accurate surgical approach and can be cost effective which is often a barrier to novel techniques however there were studies that contrasted the view of the cost efficacy. Due to the lack of published randomised controlled trials, current evidence is not strong enough to recommend the use of surgical cutting guides and customised/pre-bent plates for orthognathic surgery.